Molecular profile of the NF‐κB signalling pathway in human colorectal cancer. Issue 24 (25th November 2022) - Dobre, Maria; Trandafir, Bogdan; Milanesi, Elena; Salvi, Alessandro; Bucuroiu, Ioana Alina; Vasilescu, Catalin; Niculae, Andrei Marian; Herlea, Vlad; Hinescu, Mihail Eugen; Constantinescu, Gabriel
Abstract: The development and progression of colorectal cancer (CRC) have been associated with inflammation processes that involve the overactivation of the NF‐κB signalling pathway. The characterization of the NF‐κB expression profile in CRC is an important topic since the suppression of NF‐κB represents a potential therapeutic approach. In this study, we assessed the expression levels of 84 NF‐κB‐related genes in paired tumoral (T) and peritumoral (PT) tissues from 18 CRC patients and 18 normal colonic mucosae, and the expression levels of three miRNAs targeting the most dysregulated genes revealed by the case–control analysis. Comparing the gene expression profile of T and controls, 60 genes were dysregulated. The comparison of T and PT revealed 17 dysregulated genes in the tumoral tissues, with IL1B, CXCL8, IL1A, and CSF2 being the most upregulated. Notably, through a bioinformatics analysis, the differential gene expression of 11 out of the 17 genes was validated on a larger cohort of 308 CRC patients compared with 41 controls. Moreover, a decrease in the levels of RELA, NOD1, CASP8, BCL2L1, ELK1, and IKBKB was identified in poorly differentiated tumours compared to moderately differentiated tumours. The analysis of the three miRNAs targeting IL1B, CXCL8, IL1A, and CSF2 showed that miR‐182‐5p was upregulated in T compared with PT, whereas miR‐10b‐5p was downregulated in T compared with PT and control tissues. Our results may contribute to the design of new experimental therapeutic strategies based on endogenous molecules, such as miRNAs, to target the genetic key players of the NF‐ κB pathway.